The Use of Vocabulary Learning Strategy by Undergraduate Students - Arpinda Syifa’a Awalin (Linguistic, English Education and Art (LEEA) Journal, 2022)
Every language learner has different strategy to gain new vocabulary depending on their ability. Vocabulary learning strategy is used by undergraduate students who have vocabulary size can be found in this study. Since vocabulary as the one language aspect should be mastered, without vocabulary is nothing. Moreover, this research is conducted to investigate the vocabulary learning strategies used by undergraduate students who have high proficiency in vocabulary. The data was gained from questionnaires. In addition, the result shown that among undergraduate students who high proficiency in vocabulary used different vocabulary learning strategy based on their interest. According to three kinds oof vocabulary learning strategy (i.e., discovery, social, and consolidate strategy). By using these strategies, language learners can learn or memorize the vocabulary easily. Keywords: Vocabulary Learning Strategy, Learners who have high proficiency in vocabulary